There are no zeroes for an expression, only for equations.
Assuming equation to be
<span>−7x^2 − 91x − 280=0
-7(x^2+13x+40)=0
-7(x+8)(x+5)=0
by the zero product properties,
x+8=0 => x=-8
or
x+5=0 => x=-5</span>
Step-by-step explanation:
the volume of a cube is
side³.
since the volume is 27 m³, the individual side lengths are then the cubic root of 27 = 3 m.
the surface area is 6 squares of 3×3 = 9m², so in total
9 × 6 = 54 m²
Answer:
357
Step-by-step explanation:
5% of 340 is 17 add that to 340, the price of bicycle by itself and you get 357
Answer:
25 in
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality<u>
</u>
<u>Trigonometry</u>
[Right Triangles Only] Pythagorean Theorem: a² + b² = c²
- a is a leg
- b is another leg
- c is the hypotenuse<u>
</u>
Step-by-step explanation:
<u>Step 1: Identify</u>
Leg a = 24
Leg b = 7 in
Leg c = <em>x</em>
<em />
<u>Step 2: Solve for </u><em><u>x</u></em>
- Substitute in variables [Pythagorean Theorem]: 24² + 7² = x²
- Evaluate exponents: 576 + 49 = x²
- Add: 625 = x²
- [Equality Property] Square root both sides: 25 = x
- Rewrite/Rearrange: x = 25
Answer:
![x=\frac{30}{7}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B30%7D%7B7%7D)
Step-by-step explanation:
We have been given an equation
. We are asked to solve our given equation.
First of all, we will add
on both sides of equation to separate x variable on one side of equation.
![\frac{2}{3}x+\frac{1}{2}x=-\frac{1}{2}x+\frac{1}{2}x+5](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7Dx%2B%5Cfrac%7B1%7D%7B2%7Dx%3D-%5Cfrac%7B1%7D%7B2%7Dx%2B%5Cfrac%7B1%7D%7B2%7Dx%2B5)
![\frac{2}{3}x+\frac{1}{2}x=5](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7Dx%2B%5Cfrac%7B1%7D%7B2%7Dx%3D5)
Now, we will make a common denominator.
![\frac{2*2}{3*2}x+\frac{1*3}{2*3}x=5](https://tex.z-dn.net/?f=%5Cfrac%7B2%2A2%7D%7B3%2A2%7Dx%2B%5Cfrac%7B1%2A3%7D%7B2%2A3%7Dx%3D5)
![\frac{4}{6}x+\frac{3}{6}x=5](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B6%7Dx%2B%5Cfrac%7B3%7D%7B6%7Dx%3D5)
Add numerators:
![\frac{4+3}{6}x=5](https://tex.z-dn.net/?f=%5Cfrac%7B4%2B3%7D%7B6%7Dx%3D5)
![\frac{7}{6}x=5](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B6%7Dx%3D5)
Upon multiply both sides of our equation by
, we will get:
![\frac{6}{7}*\frac{7}{6}x=5*\frac{6}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B7%7D%2A%5Cfrac%7B7%7D%7B6%7Dx%3D5%2A%5Cfrac%7B6%7D%7B7%7D)
![x=\frac{5*6}{7}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B5%2A6%7D%7B7%7D)
![x=\frac{30}{7}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B30%7D%7B7%7D)
Therefore, the solution for our given equation is
.